Penerapan Google Sheets sebagai Sistem Otomatisasi Pencatatan Barang untuk Stok Opname di Gudang Cresta Management - Nessa Wulan Rosdiana; Roni Faslah; Rayi Dwipanilih (Saturnus: Jurnal Teknologi dan Sistem Informasi, 2026)
This research was conducted with the aim of developing an automation system for recording warehouse inventory based on Google Sheets to improve the effectiveness and efficiency of the stocktaking process at the Cresta Management warehouse. This research was based on problems in the semi-manual process that used logbooks and separate files for each group of goods, which caused problems such as data duplication, limited data access, lack of data transparency, and lengthy recapitulation process. This research used the Research and Development method using the ADDIE model (Analyze, Design, Develop, Implement, and Evaluate). Data were collected through observastion, interviews, questionnaires, and documentation. The result of this development is a system consisting of a login page, goods transcation recording, warehouse dashboard, stock reports, stock cards, and PDF report exports. This study also produced evaluation scores regarding the system’s feasibilty: 93,3% from the first media expert, 80% from the second media expert, 73,3% from the material expert, and 91,75% from users through User Acceptance Testing. These evaluation results indicate that the system is feasible for use and implementation in supporting warehouse operations, as it provides real time data updates, improves the efficiency of goods reporting, and enhances warehouse transactions.